The Maybe Monad is a simple but very useful example of a monadic computation
• We’ve already seen the Maybe type. Let’s look at the Maybe monad, which makes using the Maybe type a lot easier.

### The Maybe type constructor

You already know the definition of the Maybe type:

 data Maybe a = Just a | Nothing

### Example use of Maybe: Safe head and tail

The head and tail functions from the Prelude are not safe in the sense that they fail when called on an empty list. We can define safe versions using Maybe:

 myHead :: [a] -> Maybe a myHead [] = Nothing myHead (x:xs) = Just x myTail :: [a] -> Maybe [a] myTail [] = Nothing myTail (x:xs) = Just xs

Now we can make Maybe an instance of the Monad type class, simply by providing the appropriate definitions for return, bind, then and fail:

 import Control.Monad instance Monad Maybe where return = Just Nothing >>= f = Nothing (Just x) >>= f = f x fail _ = Nothing

There are a few additional functions defined in the MonadPlus type class:

 instance MonadPlus Maybe where mzero = Nothing Nothing mplus x = x x mplus _ = x

That’s it, we now have a Maybe monad!

Note: for users of ghc 7.10 and higher, we need to do a little bit more work.

## Explicit Maybe versus the Maybe Monad

Let’s see what this monad gives us:

### A computation using explicit Maybe

 foo :: [a] -> Maybe a foo xs = case myTail xs of Nothing -> Nothing Just a -> case myTail a of Nothing -> Nothing Just b -> myHead b

To combine computations that use the Maybe type, we need explicit case expressions to pattern match against the type.

### A computation using the Maybe monad

Let’s write this computation using the Maybe monad, first using the >>= operator:

 bar :: [a] -> Maybe a bar xs = myTail xs >>= (a -> myTail a >>= (b -> myHead b))

Now let’s change the line breaks and indentation a bit to make it look nicer:

 bar2 :: [a] -> Maybe a bar2 xs = myTail xs >>= (a -> myTail a >>= (b -> myHead b))

Thanks to the associativity law, we can also remove unnecessary parentheses:

 bar3 :: [a] -> Maybe a bar3 xs = myTail xs >>= a -> myTail a >>= b -> myHead b

This is already a lot cleaner, but finally we can use the do-notation:

 bar3 :: [a] -> Maybe a bar3 xs = do a <- myTail xs b <- myTail a myHead b

### Example: Reduction of bar [5,6]

 bar [5,6] -- > substitute [5,6] for xs in definition of bar myTail [5,6] >>= (a -> myTail a >>= (b -> myHead b)) -- > def. myTail Just [6] >>= (a -> myTail a >>= (b -> myHead b)) -- > def.2 of (>>=) (a -> myTail a >>= (b -> myHead b)) [6] -- > beta reduction, substitute [6] for a myTail [6] >>= (b -> myHead b) -- > reduce myTail Just [] >>= (b -> myHead b) -- > def.2 of (>>=)  (b -> myHead b) [] -- > beta reduction, substitute [] for b myHead [] -- > def.1 myHead Nothing

### Example: Reduction of bar [5,6,7]

 bar [5,6,7] -- > substitute [5,6,7] for xs in definition of bar myTail [5,6,7] >>= (a -> myTail a >>= (b -> myHead b)) -- > def. myTail Just [6,7] >>= (a -> myTail a >>= (b -> myHead b)) -- > def.2 of (>>=) (a -> myTail a >>= (b -> myHead b)) [6,7] -- > beta reduction, substitute [6,7] for a myTail [6,7] >>= (b -> myHead b) -- > reduce myTail Just [7] >>= (b -> myHead b) -- > def.2 of (>>=)  (b -> myHead b) [7] -- > beta reduction, substitute [7] for b myHead [7] -- > def myHead Just 7